Enhancing drought resilience and energy security through complementing hydro by offshore wind power—The case of Brazil. (1st February 2023) - Borba, Paula Conde Santos; Sousa, Wilson C.; Shadman, Milad; Pfenninger, Stefan
Abstract: During atypical droughts, power systems with a heavy reliance on hydropower risk increased greenhouse gas emissions if they are balanced with fossil-fired generation. This work investigates the role of offshore wind energy in reducing the vulnerability of power systems dependent on such hydrological patterns, thereby eliminating this emission increase, using Brazil as a case study. Offshore wind potential and its complementarity with hydro resources are addressed by considering bias-corrected reanalysis data. Then, a cost-minimizing model is built to analyze the effect of integrating wind farms (considering bottom-fixed and floating structures and distance to shore) into the existing power system in Brazil. Applying a lower, median, and upper bias correction factor, potentials are reduced by 8%–44% compared to uncorrected data. Irrespective of systematic bias, the findings indicate a high complementarity between Northeastern wind regimes and most hydropower basins. The share of offshore wind energy grows in scenarios with reduced costs, but wind farms are part of the optimal system even with the current costs. With increasing wind power capacity, dynamic dispatch changes, and natural gas no longer plays a role in the dry season as it currently does, but only in the rainy season on a significantly reduced scale. Existing reservoirs support the integration of offshore wind farms into highly renewable scenarios, but they are insufficient in a complete fossil fuel phaseout, where other electricity storage must be deployed to help balance the system. Yet, power systems in the scenarios with large wind capacity have less stored hydropower in the dry season than in the current system, while they store more in the rainy season, implying a reduced risk of empty reservoirs. The Brazilian power system with offshore wind farms can eliminate 54.4 Mton CO2 e q / y e a r (97% of current power sector emissions) without additional electricity storage. Highlights: Offshore wind potential with bias-corrected reanalysis data in Brazil. High complementarity between Northeastern wind regimes and most hydro basins. Natural gas no longer essential in the dry season in systems with a high wind share. The combination of wind and hydro storage leads to a lower risk of empty reservoirs. Addition of offshore wind can eliminate 97% of current power sector emissions.